Testing the relationship between public and private transfers : empirical evidence from South Africa - Chennells, Matthew John (School of Economics, 2016)
Financial transfers between individuals living away from their households play an important role in the reallocation of resources, particularly in developing countries. Likewise, the involvement of the State in society and public transfers of resources have been extensively documented as to their alleviation of poverty and inequality and long-term impacts on social welfare. Research has, however, shown a negative relationship between these two types of transfers. This paper adds to the literature by analysing this 'crowding out' hypothesis in a South African context, using the country's relatively generous state pension program and history of migratory remittance transfers as its basis. I use data from the first three waves of the National Income Dynamics Study, a nationally-representative panel survey from South Africa. To overcome problems of endogeneity, I use pension age-eligibility to instrument for reported pension receipt and use a sharp regression discontinuity design around the pension age-eligibility threshold to see the impact of pension receipt on the level of remittances received. The exogeneity of pension age-eligibility is critical. I first conduct my analysis using cross-sectional regressions on each wave at a household level before running an analysis on pooled panel data at an individual level. I use various transformations of the dependent variable and a range of different estimators to overcome the large presence of zero observations in and non-normal distribution of the data.